DARA JINGGA, WISRAN HADI: PARODI TERHADAP KEKUASAAN - Rusyda Ulva (SALINGKA, 2015)
This article uses Dara Jingga research was done by using the postmodern parody theory of Linda Hutcheon. Parody theory is utilized to find the implicit and explicit meanings as a new interpretation of the mythical and historical background of Dara Jingga script play. In so doing, it can reveal the author criticisms as an implementation of parodies in this act.  The result of this research points outthat the playscript of Dara Jingga is a parody of Dara Jingga or Bundo Kanduang myth and Pamalayu history text. Parody in this script play is a media used by the author to give a critical  criticisms toward power that are being passed on among others: criticizing authoritarian government form which prevents the freedom of expressing opinion, criticizing the power holder that monopolizes history, and criticizing power that is carried on with violence